ON THE WAY TO OBSERVE HOW FUTURE PRIMARY SCHOOL TEACHERS REASON ABOUT FRACTIONS - Libuše Samková; Marie Tichá (Journal on Efficiency and Responsibility in Education and Science, 2017)
In our contribution we focus on the possibility to use an educational tool called Concept Cartoons in future primary school teachers’ education, as an instrument for observing how future primary school teachers reason about fractions. In the introduction section we present Concept Cartoons, and also the primary school level of the fractions topic. In the first part of the research we analyse data obtained when future primary school teachers were solving a problem in the Concept Cartoon form. The task which we adapted to this form belongs to primary school mathematics, it focuses on the concept of a fraction per se (on the parts-and-whole decision and on comparison of two pre-partitioned models with diverse wholes). Using Concept Cartoons, we can observe which statements about the issue our respondents consider as correct, and which kinds of reasoning they use in their justifications. In the second part of the research we analyse problems that the respondents themselves posed in the Concept Cartoon form, with particular focus on tasks devoted to fractions.